Atomic Physics for Everyone An Introduction to Atomic Physics, Quantum Mechanics, and Precision Spectroscopy with No College-Level Prerequisites - Raven, Will.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access textbook introduces beginning undergraduate students and high school students to the world of quantum mechanics and atomic spectroscopy. Requiring no previous knowledge of physics and no math beyond basic algebra and sines and cosines, this book focuses on concepts to make the excitement of atomic physics more accessible for learners than ever before. It comes replete with learning goals, exercises and solutions, and an optional experimental component, making this text readily adoptable for both the classroom and the undergraduate lab. The book takes the reader on a lively and engaging tour through topics at the forefront of current science, including photons, quantum numbers, atomic energy levels, some different spectroscopy techniques, electronic structure, atomic notation, angular momentum, hyperfine structure, isotope shifts, the strong force, an introduction to the Standard Model of Particle Physics, and more. This is an open access book.
Chapter 1. Introduction to Atoms and Light -- Chapter 2. Natural Light -- Chapter 3. Atoms at rest -- Chapter 4. Atoms in Motion -- Chapter 5. Saturated Absorption Spectroscopy -- Chapter 6. Quantum Mechanics vs. Classical Physics -- Chapter 7. Angular Momentum -- Chapter 8. Electronic Structure and Atomic Notation -- Chapter 9. Hyperfine Structure -- Chapter 10. Isotope Shifts, Radioactive Decay, and the Nuclear Forces -- Chapter 11. The Standard Model of Particle Physics.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Atoms; Molecules; Optics; Spectrum analysis; Quantum physics; Materials -- Analysis; Atomic, Molecular and Chemical Physics; Optics and Photonics; Spectroscopy; Quantum Physics; Materials Characterization Technique